The Law and Institutional Aspect in Increasing the Effectiveness and Efficiency of the Coastal Area Management - Gatot D.Hendro Wibowo (Jurnal Hukum IUS QUIA IUSTUM, 2009)
This research is intended to identify the regulation and institution related to management of coastal area. Regarding the subject matter of this study, this research is a normative legal research. It employed several approach, i.e. conceptual approach and statutory approach.From this research, find out that (1) the authority of coastal area management can be found in sector regulation such as tourism, environmental, land, mining, forestry regulation, etc. It consequence that many institution will take about the coastal authority, (2) From the Institutional view, the activities of cross sector, overlapping and potentially creating a conflict of authority, all of this, need the institutional system with integration and coordinating priority, (3) The institutional approach by clear authority, strong institution and good procedure, can be increased effectively by the management of sustainable coastal area.Keywords: Institutional Approach; Effective Management of Coastal Area